Some Further Results on Oscillations for Neutral Delay Differential Equations with Variable Coefficients - Fatima N. Ahmed; Rokiah Rozita Ahmad; Ummul Khair Salma Din; Mohd Salmi Md Noorani (Abstract and Applied Analysis)
We study the oscillatory behaviour of all solutions of first-order neutral equations with variable coefficients. The obtained results extend and improve some of the well-known results in the literature. Some examples are given to show the evidence of our new results.